TINDAK TUTUR DIREKTIF GURU BAHASA INDONESIA DAN RESPONS SISWA DALAM PROSES BELAJAR MENGAJAR DI KELAS X AKUNTANSI KEUANGAN DAN LEMBAGA 3 SMK NEGERI 3 PADANG - Banjarnahor, Dame; Noveria, Ena (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research, namely. First, describe the form of the Indonesian language teacher directive speech act in PBM in class X AKL 3 of SMK Negeri 3 Padang. Second, describe the teacher's speaking strategy. Third, describing the context for using spoken strategies. Fourth, describe student responses. This type of research is qualitative research with descriptive methods. The data in this research are teacher directive speech acts and student responses. Data was collected by recording techniques, and recorded. Data analysis techniques, namely first, transcribe the recorded data into written language. Second, inventory and identify speech acts. Third, classify data based on the type of speech. Fourth, analyzing the data based on the form of speech acts, speaking strategies, the context of speaking situations, and student responses. Fifth, conclude data based on data collection.The results of this research are four. First, the form of the Indonesian teacher's directive speech act. Second, the strategy of speaking Indonesian teachers in PBM.Third, the context of using speech strategies.Four, student responses to the form of teacher directive speech acts.Â Kata Kunci: Tindak Tutur Direktif, Guru, Respons Siswa